Answer:
23. 16x² + 4x + 0.25
24. 16x² - 4x + 0.25
Explanation:
Given the functions f(x) = 4x + 0.5 and g(x) = 4x - 0.5, questions 23 and 24 are asking you to square the entire function. So, you will take the expression given in each function and square it:
(f(x))² = (4x + 0.5)(4x + 0.5) Using FOIL:
(4x*4x) + (4x*0.5) + (4x*0.5) + (0.5*0.5)
16x² + 2x + 2x + 0.25 = 16x² + 4x + 0.25
(g(x))² = (4x - 0.5)(4x - 0.5) Using FOIL:
(4x*4x) - (4x*0.5) - (4x*0.5) + (0.5*0.5)
16x² - 2x - 2x + 0.25 = 16x² - 4x + 0.25